2016
DOI: 10.1002/ijc.30372
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral therapy improves overall survival in hepatitis C virus‐infected patients who develop diffuse large B‐cell lymphoma

Abstract: Chronic Hepatitis C virus (HCV) infection is associated with increased incidence of non-Hodgkin lymphoma. Several studies have demonstrated regression of indolent lymphoma with antiviral therapy (AVT) alone. However, the role of AVT in HCV-infected patients with diffuse large B-cell lymphoma (DLBCL) is unclear. We therefore analyzed AVT’s impact on oncologic outcomes of HCV-infected patients (cases) who developed DLBCL. Cases seen at our institution (June 2004-May 2014) were matched with uninfected counterpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 40 publications
0
48
1
1
Order By: Relevance
“…In our population, none of the patients presented with HBV and HIV coinfection and, as in other studies, the age‐adjusted incidence of lymphoid and related tissue cancers was higher when compared to the general French population (SMR, 2.03; 95% CI, 1.11‐3.41; P = 0.023), which also applied to patients without any cancer risk factors (SMR, 2.08; 95% CI, 1.14‐3.50; P = 0.019) and those without an SVR (SMR, 2.74; 95% CI, 1.18‐5.40; P = 0.021). In some studies, the clearance of HCV infection was associated with a reduction in hematological malignancies, a better response to chemotherapy, and an improvement in overall survival . Interestingly, the age‐adjusted incidence of lymphoid and related tissue cancers was higher when compared to the general French population, independently of the existence of risk factors and SVR achievement.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our population, none of the patients presented with HBV and HIV coinfection and, as in other studies, the age‐adjusted incidence of lymphoid and related tissue cancers was higher when compared to the general French population (SMR, 2.03; 95% CI, 1.11‐3.41; P = 0.023), which also applied to patients without any cancer risk factors (SMR, 2.08; 95% CI, 1.14‐3.50; P = 0.019) and those without an SVR (SMR, 2.74; 95% CI, 1.18‐5.40; P = 0.021). In some studies, the clearance of HCV infection was associated with a reduction in hematological malignancies, a better response to chemotherapy, and an improvement in overall survival . Interestingly, the age‐adjusted incidence of lymphoid and related tissue cancers was higher when compared to the general French population, independently of the existence of risk factors and SVR achievement.…”
Section: Discussioncontrasting
confidence: 99%
“…A sustained viral response (SVR) in HCV patients and maintained viral suppression (MVR) by nucleos(t)ide analogues in HBV patients have changed the clinical course of viral cirrhosis during recent decades. Several studies have suggested a lower incidence of liver‐related complications as well as the regression of NHL following viral control or eradication . The long‐term follow‐up of patients with a negative HBV viral load and SVR is now the next challenge as these patients are going to live for longer and will therefore be exposed to extrahepatic complications like EHC, as is observed in the general population.…”
mentioning
confidence: 99%
“…The findings of our study confirm the high frequency and aggressive nature of CD5‐positive DLBCL cells in HCV‐infected patients. It may also explain, at least in part, the high relapse rate of CD5‐positive DLBCL seen in this study and the HCV‐driven resistance of DLBCL to chemotherapy we observed in our previous work …”
Section: Discussionmentioning
confidence: 53%
“…This was recently echoed in a meta-analysis conducted by Peveling-Oberhag et al [10], who found that achievement of SVR was associated with a higher rate of clinical response to lymphoma (73% response vs 53% response; 95% CI 39–67%; P < .05). The benefit of antiviral therapy in patients with HCV-associated DLBCL has also been associated with improved 5-year overall survival rates when compared with those who did not receive treatment for their HCV infection [11, 12]. …”
Section: Discussionmentioning
confidence: 99%